Antidiarrheal Effectiveness Test of Ketapang Leaf Infusion (Terminalia catappa L.) Against Male Mice (musculus) - Polontalo, Nani Astria; Marlina, Ni Ketut; Nuraisya, Nuraisya; Febrita, Veny (Rifa'Institute, 2025)
Introduction: Diarrhea is a common health problem that can be serious if not treated immediately. Ketapang leaves (Terminalia catappa L.) contain active compounds such as tannins and alkaloids which are known to have antibacterial activity and have the potential as an antidiarrheal drug. Objective: This study aims to evaluate the effectiveness of ketapang leaf infusion in treating diarrhea and to determine the most optimal dose in male mice (Mus musculus). Method: The experimental study was conducted using the infusion method on 15 male mice divided into five treatment groups, namely negative control (Na CMC), positive control (loperamide), and three test groups with ketapang leaf infusion at concentrations of 25%, 50%, and 75%. Diarrhea was induced using oleum ricini, and the number of stools was monitored 180 minutes after treatment. Analysis was performed using an independent T-test. Result and Discussion: The results showed that 50% and 75% ketapang leaf infusions provided the highest stool reduction effect compared to the other groups. Conclusion: In conclusion, ketapang leaf infusion has potential as an antidiarrheal agent, with concentrations of 50% and 75% as the most effective doses in this study.